Theoretical Study of the Resveratrol Adsorption on B12N12 and Mg‐Decoration B12N12 Fullerenes. (21st April 2021) - Sheikhi, Masoome; Azarakhshi, Fatemeh; Tafreshi, Elnaz Sarabadani; Kaviani, Sadegh; Shahab, Siyamak; Ahmadianarog, Mahin
Abstract : The adsorption of Resveratrol (RSV) drug on surfaces of the pure B12 N12 and Mg‐decoration B12 N12 fullerenes at physiological PH was studied using density functional theory and time‐dependent density functional theory methods at the B3PW91/6‐31+G* level at T  = 298.15 K and 1 atm in the solvent (water) with a dielectric constant of 78.4. The adsorption energy ( E ads ) of RSV on two fullerenes have investigated through hydroxyl (‐OH) groups. The adsorption effect of the RSV on the bond lengths, electronic properties, UV spectra, and excited states of B12 N12 and Mg‐B12 N12 is detected. Natural bond orbital analysis shows a charge transfer between the RSV and two fullerenes. The electron location function (ELF) and localized orbital locator (LOL) values show that interaction between reactive atoms of RSV (O atoms) and B atom of B12 N12 are an electrostatic and partially covalent character. The study interaction of RSV with the B12 N12 and Mg‐decoration B12 N12 can be used in the field of drug delivery and adsorption on metal surfaces. Abstract : We studied the adsorption of Resveratrol (RSV) drug on surfaces of the pure B12 N12 and Mg‐decoration B12 N12 fullerenes using density functional theory and time‐dependent density functional theory method at the B3PW91/6‐31+G* level of theory. The adsorption of RSV on two fullerenes is an exothermic process. The adsorption effect of the RSV molecule on the bond lengths, electronic properties, dipole moment, UV absorption spectra, and excited states and of B12 N12 and Mg‐B12 N12 fullerenes is investigated. Natural bond orbital analysis shows a charge transfer between the RSV and two fullerenes. The high electron location function (ELF) and localized orbital locator (LOL) values show that interaction between reactive atoms of RSV and B atom of B12 N12 are an electrostatic and partially covalent character.